Nicotine enhances object recognition memory through inhibition of voltage-dependent potassium 7 channels in the medial prefrontal cortex of mice - Hirohito Esaki; Shoma Izumi; Akari Fukao; Naoya Nishitani; Satoshi Deyama; Katsuyuki Kaneda (Elsevier, 2021)
Nicotine administration enhances object recognition memory. However, target brain regions and cellular mechanisms underlying the nicotine effects remain unclear. In mice, the novel object recognition test revealed that systemic nicotine administration before training enhanced object recognition memory. Moreover, this effect was inhibited by infusion of retigabine, a selective voltage-dependent potassium 7 (Kv7) channel opener, into the medial prefrontal cortex (mPFC) before nicotine administration. Additionally, infusion of XE-991, a selective Kv7 channel blocker, into the mPFC before training enhanced object recognition memory. Therefore, Kv7 channels in the mPFC may be at least partly involved in nicotine-induced enhancement of object recognition memory.